Tunable discontinuous shear thickening in capillary flow of MR suspensions. (July 2021) - Bossis, Georges; Grasselli, Yan; Ciffreo, Alain; Volkova, Olga
Very concentrated suspensions of iron particles in water or ethylene glycol can be obtained thanks to the use of superplasticizer molecules used in cement industry. At high volume fractions, these suspensions show a discontinuous shear thickening which was thoroughly characterized in rotational geometries. We will show that the jamming transition is also present in a capillary flow, and that it manifests through the formation of a non-consolidated porous medium at the constriction between the barrel and the capillary. In suspension of iron particles, the dynamics of formation of this porous medium, and so the pressure, can be controlled by a low magnetic field and is reversible for a constant volume flow rate, opening potential new applications in the domain of dampers and force control devices.